A genetic polymorphism of IL17F rs763780 associated with anti-E production in the Han Chinese population. (August 2020) - Chen, Sitian; Xiao, Jie; Song, Ning; Xu, Haixia; Tian, Li; Liu, Zhong
Abstract: Objective: This study aimed to investigate the association among 4 single nucleotide polymorphisms (SNPs) in the genes TLR3, IL17F, ERAP1 and ERAP2 with anti-E alloantibody production. Background: Anti-E alloantibodies can lead to clinically significant delayed hemolytic transfusion reactions (DHTRs) and hemolytic disease of the newborn (HDN). Some individuals produce anti-E alloantibodies post- transfusion. The mechanisms controlling this process is poorly understood. Methods: Ninety-five patients with anti-E alloantibodies were enrolled, and samples from 186 healthy donors were used as controls. Four SNPs in the immune-related genes ( TLR3, IL17F, ERAP1 and ERAP2 ) were selected. SNPs were analyzed by polymerase chain reactions (PCR) and TaqMan assays. Allele and genotype frequencies were compared using Pearson's chi-square test. Results: The C allele and CC + CT genotypes of rs763780 in the IL17F gene were overrepresented in the E- alloimmunized patient group (14.2 % vs. 5.1 %, P < 0.001; 23.2 % vs. 9.7 %; P = 0.004). Individuals with CC + CT genotypes of rs763780 had a higher risk of E-alloimmunization. (OR, 2.81; 95 % CI, 1.42–5.56). No significant difference was observed among the other 3 SNPs. Conclusions: SNP rs763780 in the IL17F gene was associated with E-alloimmunization in a sample of the Han Chinese population, with the allele C as a risk allele.